Analisis Perbandingan Hukum Perdata dan Hukum Islam pada Perkawinan di Bawah Umur - Adha’ifa, Aisyaira Diya; Romandani, Alif Wulan; Kori, Angelika Tasya; Mardiana, Atia; Rahmawati, Dewi; Hayulenda, Fhazry Eka; Matussilmi, Fina Ida; Hafizha, Naura; Amiarti, Rizky Dini; Dewi, Shella Kartika; Agustinus, Syeren Welda; Ummah, Syifa Khoirul (UNIVERSITAS SERAMBI MEKKAH, 2025)
Law No. 1 of 1974 establishes a minimum age of 19 years for marriage with court permission, while Islamic law emphasizes physical and mental maturity without a specific age limit. This study compares the two legal systems in handling underage marriages with a focus on child rights protection and norm alignment. This research aims to understand the main issues related to underage marriage through a comparative analysis between civil law and Islamic law. Additionally, this study examines the policies and roles of marriage registration institutions in protecting the rights and interests of children. This research uses qualitative methods with literature study techniques to analyze the differences between civil law and Islamic law regarding underage marriage. Data from Law No. 1 of 1974, interpretations of Islamic law, and journals are descriptively analyzed to produce relevant recommendations. The research results show that the rules regarding the minimum age limit are not yet consistent, leading to the frequent occurrence of underage marriages. This indicates the importance of a more in-depth evaluation of granting permission for underage marriages, as regulated in the Supreme Court Regulation (PERMA) No. 5 of 2019, which states that the marriage process must consider several aspects such as health, education, and social conditions to ensure a good decision for the child.